2020
DOI: 10.2147/jpr.s242825
|View full text |Cite
|
Sign up to set email alerts
|

<p>Safe Opioid Storage and Disposal: A Survey of Patient Beliefs and Practices</p>

Abstract: Objective: To evaluate knowledge, practices, and beliefs of US patients receiving prescription opioids regarding opioid storage, disposal, and diversion. Design: Internet-based, cross-sectional survey conducted between September and October 2018. Fisher's exact tests and Kendall's Tau-c were used to assess associations with storage and disposal outcomes. Participants: Patients aged ≥18 years with acute (n=250) or chronic noncancer (n=250) pain were prescribed an oral opioid within 90 days of the survey. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…A study was conducted in the United States to evaluate the knowledge and practices among patients receiving opioids; results revealed that patients who received counseling about proper storage of medications kept their medicines in locked place, compared for those who didn't ( P < 0.00001)[ 27 ]…”
Section: Discussionmentioning
confidence: 99%
“…A study was conducted in the United States to evaluate the knowledge and practices among patients receiving opioids; results revealed that patients who received counseling about proper storage of medications kept their medicines in locked place, compared for those who didn't ( P < 0.00001)[ 27 ]…”
Section: Discussionmentioning
confidence: 99%
“…Communities have the option of selecting a strategy to promote safe disposal practices such as the installation of permanent disposal kiosks or the implementation of other disposal programs such as distribution of drug mail-back envelopes. Studies have shown that leftover medication from an opioid prescription is common ( Bicket et al, 2017 ; Kennedy-Hendricks et al, 2016 ) and that patient education regarding disposal practices can increase opioid disposal rates ( Hasak et al, 2018 ), although education about disposal is suboptimal ( Gregorian et al, 2020 ). According to a recent study, only 30% of persons who had received an opioid prescription in the previous two years disposed of their unused opioid medication; however, over 80% indicated they would be more likely to dispose of opioid medications in the future if disposal kiosks were in a location they visited frequently ( Buffington et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Selective serotonin reuptake inhibitors (SSRIs), nonsteroidal inflammatory drugs (NSAIDs), acetaminophen (APAP), histamine-1 receptor antagonists (H1RAs), and sedatives/hypnotics/antipsychotics (SHAs) have been identified as medications commonly involved in child poisoning in the NPDS reports [12][13][14]28,29]. Opioids have also been identified as harmful and high-risk medications for poisoning of minors [35][36][37][38][39][40][41][42][43][44][45]. Regardless of the types of medications, the ease of access seems to play a significant role in pediatric exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Storing in closed spaces like drawers and closets would also provide additional physical barriers and keep medications away from children more effectively. Nevertheless, for opioids which are extremely habit forming, two studies found that 26% and 36% of the participants stored them in open spaces at home, respectively, noting unsafe storage of the high-risk medication [37,38].…”
Section: Introductionmentioning
confidence: 99%